2004
DOI: 10.3171/jns.2004.101.6.1004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution kinetics of targeted cytotoxin in glioma by bolus or convection-enhanced delivery in a murine model

Abstract: These studies provide confirmation of a previous hypothesis that CED of IL-13 cytotoxin is superior to bolus injections not only for the safety of the normal brain but also for maintaining drug levels for a prolonged period in infused brain tumors. These findings are highly relevant and important for the optimal clinical development of IL-13 cytotoxin or any other targeted antitumor agent for GBM therapy, in which multiple routes of delivery of an agent are being contemplated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…On the other hand, a single intratumoral administration of the protein formulations led to lower antitumor efficacy; that is, Cintredekin Besudotox doubled the median survival and all of the animals succumbed to tumor burden, and the second-generation mhIL-13-PE protein formulation elicited ∼40% long-term survival. These results suggest that the short half-life of the protein formulations (16,17) can be overcome by Ads, which allow sustained local expression.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…On the other hand, a single intratumoral administration of the protein formulations led to lower antitumor efficacy; that is, Cintredekin Besudotox doubled the median survival and all of the animals succumbed to tumor burden, and the second-generation mhIL-13-PE protein formulation elicited ∼40% long-term survival. These results suggest that the short half-life of the protein formulations (16,17) can be overcome by Ads, which allow sustained local expression.…”
Section: Discussionmentioning
confidence: 79%
“…Due to the short half-life of the hIL-13-PE protein formulation (16,17), multiple injections or continued delivery was necessary to achieve therapeutic levels (1,16,18). This approach was tested preclinically and in phase I-III clinical trials (16)(17)(18). However, in spite of high expectations, the phase III trial failed to achieve clinical endpoints (http://www.fiercebiotech.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, recent studies show that convection-enhanced delivery (CED) of IT is superior to bolus injection of IT. 49 Investigators compared the concentration of 14 Csucrose in rat brain via intravenous, intrathecal and convectionenhanced delivery and found that convection-enhanced delivery resulted in 10,000-fold increase in tissue concentration of 14 Csucrose versus intravenous delivery. 50 Others have demonstrated that CED of 125 I-boronated epidermal growth factor into rat brains with glioma tumor resulted in 47.4% injected dose/gram (IDg) of the IT being detected within the tumor bed even after 24 hr, whereas intratumoral injection of the IT resulted in only 33% ID/g being detected within the tumor bed 24 hr after injection.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-13 toxin has been shown to exert a potent cytotoxic effect in most human glioblastoma cells tested in culture (174,178,180) and in vivo, in human xenografts consisting of glioma cells implanted in the flank of nude mice (181). Moreover, the intratumoral administration of ILI3-PE toXin into intracranial human glioma xenografts in mice showed highly cytotoxic effects without undesirable side effects (182). To optimize the targeting of GBM associated IL-13cx2 receptor, human IL-13 (hIL-13) gene has been engineered leading to a mutated fonD of hIL-13 that exhibits 50 fold higher affinity for the IL13cx2 receptor present in human glioma cells when compared to the wild type IL-13 (183,184).…”
Section: Targeted Toxins For Glioma Therapymentioning
confidence: 99%